1984
DOI: 10.1159/000469482
|View full text |Cite
|
Sign up to set email alerts
|

CDP-Choline Does Not Inhibit Erythrocyte Glycolytic or Pentose Phosphate Pathway Enzyme Activity

Abstract: An increased concentration of cytidine diphosphocholine (CDP-choline) has been observed in erythrocytes in the hemolytic anemia due to hereditary pyrimidine 5'- nucleotidase deficiency (P5Nase, EC 3.1.3.5) and in a patient with a chronic hemolytic anemia not due to P5Nase deficiency, as reported by Paglia and co-workers in 1983. In the current studies, we were unable to demonstrate a significant inhibitory effect of 4 mmol/l CDP-choline on the activities of the enzymes of the Embden-Meyerhof and pentose phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In their original description, Valentine et al(19 74) speculated that the pyrimidine nucleotides might adversely dffect the metabolism of the P5N deficient RBC by competing with the purine nucleotide substrates of critical glycolytic kinases, or by consuming ATP as a cofactor for the pyrimidine nucleotide mono-and diphosphate kinases. Subsequent studies from this laboratory have suggested that certain pyrimidine nucleotides could indeed inhibit the in vitro activities of critical glycolytic enzymes at nucleotide concentrations found in the PSN deficient RBC (Tomoda et al, 1982;Oda et al, 1984: Lachant & Tanaka, 1984. Although these studies suggested that impaired antioxidant defence and/or impaired glycolysis should be responsible, in part, for the shortened RBC survival seen in hereditary P5N deficiency, no evidence has, as yet, been found in the pattern of glycolytic intermediates (Buc et al, 1979;Beutler et al, 1980: Oda et al, 1984 for an in vivo metabolic block at the levels predicted by in vitro studies.…”
Section: Dtscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their original description, Valentine et al(19 74) speculated that the pyrimidine nucleotides might adversely dffect the metabolism of the P5N deficient RBC by competing with the purine nucleotide substrates of critical glycolytic kinases, or by consuming ATP as a cofactor for the pyrimidine nucleotide mono-and diphosphate kinases. Subsequent studies from this laboratory have suggested that certain pyrimidine nucleotides could indeed inhibit the in vitro activities of critical glycolytic enzymes at nucleotide concentrations found in the PSN deficient RBC (Tomoda et al, 1982;Oda et al, 1984: Lachant & Tanaka, 1984. Although these studies suggested that impaired antioxidant defence and/or impaired glycolysis should be responsible, in part, for the shortened RBC survival seen in hereditary P5N deficiency, no evidence has, as yet, been found in the pattern of glycolytic intermediates (Buc et al, 1979;Beutler et al, 1980: Oda et al, 1984 for an in vivo metabolic block at the levels predicted by in vitro studies.…”
Section: Dtscussionmentioning
confidence: 99%
“…3.1.3.5)] (P5N) results in a chronic, nonspherocytic haemolytic anaemia (Valentine et aI, 1974;Paglia & Valentine, 1980). The mechanisms responsible for the shortened red blood cell (RBC) survival remain to be completely elucidated (Valentine et al, 1974: Harley et al, 1978Torrance & Whittaker, 1979;Tomoda et al, 1982;Oda et al, 1984;Swanson et al, 1984;Lachant & Tanaka, 1984). The PSN deficient RBC contains an increased content of the cytidine and uridine tri-, di-and monophosphate nucleotides and their derivatives (Torrance 81 Whittaker, 1979;Ericson et al, 1983: Swanson et af, 1983.…”
mentioning
confidence: 99%